2019
DOI: 10.1088/1361-6463/ab199b
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency of a nanosecond repetitively pulsed discharge for methane reforming

Abstract: The performance of a nanosecond repetitively pulsed discharge for CH 4 reforming is studied at atmospheric pressure for temperatures ranging from 300 to 700 K. The high-voltage pulser used is capable of producing a voltage pulse with an amplitude of 14 kV and a duration of 40 ns at a repetition frequency of 10 kHz. The discharge energy per pulse is varied in a range from 462 µJ to 2.47 mJ. The rotational temperature is estimated by fitting synthetic to experimental spectra. Experiments at pulsing frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Also, due to a high reduced electric field, they can generate high densities of charged particles at low values of specific deposited energy, which leads to higher energy efficiencies. All the above-mentioned features can be controlled by a wide range of adjustable parameters of pulsed power supply such as pulse repetition frequency, pulse shape, pulse rise time, pulse fall time, pulse width, and pulse voltage amplitude [16,21,[32][33][34].…”
Section: Non-oxidative Coupling Of Methanementioning
confidence: 99%
See 1 more Smart Citation
“…Also, due to a high reduced electric field, they can generate high densities of charged particles at low values of specific deposited energy, which leads to higher energy efficiencies. All the above-mentioned features can be controlled by a wide range of adjustable parameters of pulsed power supply such as pulse repetition frequency, pulse shape, pulse rise time, pulse fall time, pulse width, and pulse voltage amplitude [16,21,[32][33][34].…”
Section: Non-oxidative Coupling Of Methanementioning
confidence: 99%
“…This includes life cycle assessment and eco-efficiency analysis at industrial scale in process engineering field [10,11], and making synergy between plasma and catalysts to control the selectivity of products, product yield and conversion rate in chemistry field [12][13][14][15]. In plasma physics field, the focus is on the design of new plasma reactors and application of different discharge types for the purpose of controlling and tuning the reaction mechanism, heat transfer rate, and, more important, increasing energy efficiency [16][17][18][19][20][21]. The methane conversion processes are classified in two main areas: (i) oxidative conversion to syngas or C 1 -oxygenates and (ii) non-oxidative conversion to C 2 H 4 and C 3 H 6 as the desired products.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of inlet gas temperature on CO2 and CH4 conversions and H2 and CO yields for RGA discharge is still not clear. Maqueo et al [2] reported that preheating the inlet gas did not affect the plasma-assisted dry reforming reaction in a nanosecond pulsed discharge. Zhou et al [12] reported that increasing the temperature up to 250 ºC in a DBD reactor hardly influenced the conversion of CO 2 and CH4.…”
Section: Effect Of Inlet Gas Temperaturementioning
confidence: 99%
“…The world is moving towards the use of greener and renewable technologies to meet the ever increasing energy demand; however, fossil fuels are still important in our current energy mix [1]. With the dependence on fossil fuels, the emission of pollutants, such as greenhouse gases (GHG) is an unavoidable problem [2]. Climate change is the major consequence of the enormous amount of greenhouse gases released to the atmosphere, with global and local effects such as an increase in the atmospheric temperature, massive ice melting, ocean acidification, and an enhanced rate of violent localized atmospheric events [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the uniformity of the discharge can be optimized well by applying the nanosecond pulsed power [17]. In general, the nanosecond pulsed power has a higher energy efficiency and can prevent the glow-to-arc transition [18,19]. Thus, it has been the preferred choice for us to initiate packed bed DBD, and it needs to be researched and applied.…”
Section: Introductionmentioning
confidence: 99%